2019
DOI: 10.1186/s12896-019-0542-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved the expression level of active transglutaminase by directional increasing copy of mtg gene in Pichia pastoris

Abstract: Background The microbial transglutaminase (MTG) is inactive when only the mature sequence is expressed in Pichia pastoris. Although co-expression of MTG and its N-terminal pro-peptide can obtain the active MTG, the enzyme activity was still low. One of the basic steps for strain improvement is to ensure a sufficient level of transcription of the heterologous gene, based on promoter strength and gene copy number. To date, high-copy-number recombinants of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…That is a result of the negative effects of a high concentration of target protein on the growth and metabolism of the strain [40][41][42]. Song et al (2019) reported that a co-expressing strain (pro/rDNA-mtg) with three copies of mtg genes (mtg-3c) exhibited higher transglutaminase activity than mtg-2c, mtg-6c, or mtg-8c [25]. Dagar et al (2018) reported that the expression of human interleukin-3 protein increased with the addition of up to 8 copies of the expression cassettes, then drastically decreased thereafter [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is a result of the negative effects of a high concentration of target protein on the growth and metabolism of the strain [40][41][42]. Song et al (2019) reported that a co-expressing strain (pro/rDNA-mtg) with three copies of mtg genes (mtg-3c) exhibited higher transglutaminase activity than mtg-2c, mtg-6c, or mtg-8c [25]. Dagar et al (2018) reported that the expression of human interleukin-3 protein increased with the addition of up to 8 copies of the expression cassettes, then drastically decreased thereafter [26].…”
Section: Discussionmentioning
confidence: 99%
“…Currently recombinant K. phaffii strains with high copy numbers can only be obtained by increasing gene concatemers, so alternative methods for generating multicopy strains rapidly and reliably are highly desirable [25]. Additionally, in order to study the effects of different promoters on protein expression levels, it is necessary to accurately and quantitatively analyze the copy number of foreign genes inserted into the recombinant yeast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation might be attributed to occur multi-copy integration of GFP gene into the genomes of yeast cells forming 4 th colony (Fig. 7 E) 42,43 . Comparing with LiCl or electroporation methods (Table 2), the suggested magnetotransformation system achieved an efficient transformation and resulted in sufficient numbers of transformants.…”
Section: Magneto-transformationmentioning
confidence: 99%
“…Multi-copy integration is anticipated to occur by single homologous recombination during integration, resulting in tandem integrated copies of the vector 20 .The copy number of genes for TG expression is an important factor. In pichia pastoris, TG with 3 copy numbers recorded the best activity of 1.41U/ml 21 .Therefore, the co-expression strain was selected on YPD with two concentration of G418 (contains 100 ug/ml, 150ug/ml) to ensure the successful transformant and appropriate copy number selection for TG expression. Strategy for multi-site integration of pro-region via rDNA and selection of an appropriate copy of TG produced 3.9u/ml in the shake flask, indicating the role of pro-region in proper folding of more enzyme extracellularly (Fig 3a and 3b).…”
Section: Constructing the Co-expressing Strains For Pro-and Tgmentioning
confidence: 99%